Customer Satisfaction Evaluation At Sapadia Guest House Through Servqual And Csi Approaches Based On Information Systems - Damanik, Chrisdian; Drago, Vicky; Windasari Siallagan, Melan; Jaya Harmaja, Okta (CV. Inara, 2025)
This study aims to evaluate customer satisfaction levels at Guest House Sapadia by integrating the SERVQUAL method and the Customer Satisfaction Index (CSI) within an information system-based framework. The SERVQUAL method is employed to assess service quality across five core dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Concurrently, the CSI method provides a quantitative overview of overall customer satisfaction, grounded in the perception and relative importance of each service attribute. Data were collected via an online questionnaire completed by 184 respondents and processed through a web-based information system to generate interactive visualizations and automated analyses. The results indicate that Guest House Sapadia achieved a CSI score of 84.57%, which falls under the